2021
DOI: 10.3389/fcell.2021.676356
|View full text |Cite
|
Sign up to set email alerts
|

Priming With Toll-Like Receptor 3 Agonist Poly(I:C) Enhances Content of Innate Immune Defense Proteins but Not MicroRNAs in Human Mesenchymal Stem Cell-Derived Extracellular Vesicles

Abstract: Mesenchymal stem cells (MSCs) help fight infection by promoting direct bacterial killing or indirectly by modulating the acute phase response, thereby decreasing tissue injury. Recent evidence suggests that extracellular vesicles (EVs) released from MSCs retain antimicrobial characteristics that may be enhanced by pretreatment of parent MSCs with the toll-like receptor 3 (TLR3) agonist poly(I:C). Our aim was to determine whether poly(I:C) priming can modify EV content of miRNAs and/or proteins to gain insight … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 63 publications
0
19
0
Order By: Relevance
“…In this review, we mainly focus on MSC-Exos, but studies on MSC-EVs or MSC-MVs are also included in consideration of comprehensiveness. Proteomic ( Pierce and Kurata, 2021 ), metabolic, lipidomic ( Showalter et al, 2019 ), and miRNA-sequence analysis ( Shao et al, 2017 ; Zhao et al, 2019a ) and experimental studies have indicated that MSC-Exos inherit similar biological properties from their parent cells, in aspect of immunomodulation ( Willis et al, 2018 ), tissue repair promotion ( Shao et al, 2017 ) and homing capacity ( Shao et al, 2017 ; Guo et al, 2019 ), which are important properties for treatments of microbial diseases. What is more, exosome therapy is superior to stem cell therapy in biosafety.…”
Section: Microbial Disease Therapeuticsmentioning
confidence: 99%
See 2 more Smart Citations
“…In this review, we mainly focus on MSC-Exos, but studies on MSC-EVs or MSC-MVs are also included in consideration of comprehensiveness. Proteomic ( Pierce and Kurata, 2021 ), metabolic, lipidomic ( Showalter et al, 2019 ), and miRNA-sequence analysis ( Shao et al, 2017 ; Zhao et al, 2019a ) and experimental studies have indicated that MSC-Exos inherit similar biological properties from their parent cells, in aspect of immunomodulation ( Willis et al, 2018 ), tissue repair promotion ( Shao et al, 2017 ) and homing capacity ( Shao et al, 2017 ; Guo et al, 2019 ), which are important properties for treatments of microbial diseases. What is more, exosome therapy is superior to stem cell therapy in biosafety.…”
Section: Microbial Disease Therapeuticsmentioning
confidence: 99%
“…In addition, protein profiling of MSC-EVs reveals that exosomal proteins are related to biological process such as innate immunity, antimicrobial, host-virus interaction, cellular oxidant detoxification, and complement and coagulation cascades. Several AMPs were identified, including dermcidin, lactoferrin, lipocalin 1, lysozyme C, neutrophil defensin 1, S100A7 (psoriasin), S100A8/A9 (calprotectin), and histone H4 ( Pierce and Kurata, 2021 ). AMPs partially account for the antimicrobial effects of MSCs’ secretome, which may also work in terms of MSC-Exos ( Alcayaga-Miranda et al, 2017 ).…”
Section: Mesenchymal Stem Cell-derived Exosomesmentioning
confidence: 99%
See 1 more Smart Citation
“…MSCs, exosomes secreted by these cells can be used as complementary antimicrobial agents, as a substitute for or in combination with antibiotics under specific physiological conditions or specific priming conditions [146]. In particular, antimicrobial properties are associated with the paracrine of several antimicrobial peptides (AMP), which have a wide range of antimicrobial properties, as well as specific extracellular vesicle (EV) secretion, including the release of immunomodulatory factors MSCs that retain antimicrobial properties [147] and are considered safer than parental cell administration [148]. EVS as a cell-free agent and/or drug carrier may have therapeutic effects for sepsis [148] and may be developed as a superior drug delivery vehicle [149].…”
Section: Anti-inflammatory and Antimicrobial Vesiclesmentioning
confidence: 99%
“…MSC features include the detection of infection signals, the ability to migrate toward the infection site, and on-demand secretion of combinations of antimicrobial peptides (AMPs) [16]. The EVs released from MSCs retain antimicrobial characteristics [13] and are considered to be safer than parent cell administration [17]. The EVs as cell-free agents and/or drug carriers may have therapeutic functions in sepsis [18] and may evolve into superior drug delivery tools.…”
Section: Introductionmentioning
confidence: 99%